Sindbis virus neutralising antibodies detected in Swedish horses - Agnes Björnström; Anne-Lie Blomström; Manish Chandra Singh; Jenny C. Hesson (One Health, 2021)
A number of viruses transmitted by mosquitoes are well known to cause disease in both humans and horses, ranging from mild fevers to mortal neurological disease. A recently discovered connection between the alphavirus Sindbis virus (SINV) and neurological disease in horses in South Africa initiated this serological study in northern Europe, where the same genotype of SINV (SINV-I) is also highly endemic. We tested 171 serum samples, originally obtained from horses for other reasons from April to October 2019, for presence of SINV neutralising antibodies using a plaque reduction neutralisation test (PRNT). The serum from six horses reduced the plaque count more than 80%, and two out of these reduced the plaque count more than 90%. These horses were sampled in six different regions of Sweden, and included individuals sampled from April to August. This study shows that horses in Sweden have become infected with SINV and developed neutralising antibodies. Potential connections between infection and development of disease are important questions for future studies.